Adaptive multi-paddock grazing enhances soil carbon and nitrogen stocks and stabilization through mineral association in southeastern U.S. grazing lands. (15th June 2021) - Mosier, Samantha; Apfelbaum, Steven; Byck, Peter; Calderon, Francisco; Teague, Richard; Thompson, Ry; Cotrufo, M. Francesca
Abstract: Grassland soils are a large reservoir of soil carbon (C) at risk of loss due to overgrazing in conventional grazing systems. By promoting regenerative grazing management practices that aim to increase soil C storage and soil health, grasslands have the potential to help alleviate rising atmospheric CO2 as well as sustain grass productivity across a vast area of land. Previous research has shown that rotational grazing, specifically adaptive multi-paddock (AMP) grazing that utilizes short-duration rotational grazing at high stocking densities, can increase soil C stocks in grassland ecosystems, but the extent and mechanisms are unknown. We conducted a large-scale on-farm study on five "across the fence" pairs of AMP and conventional grazing (CG) grasslands covering a spectrum of southeast United States grazing lands. We quantified soil C and nitrogen (N) stocks, their isotopic and Fourier-transform infrared spectroscopy signatures as well as their distribution among soil organic matter (SOM) physical fractions characterized by contrasting mechanisms of formation and persistence in soils. Our findings show that the AMP grazing sites had on average 13% (i.e., 9 Mg C ha −1 ) more soil C and 9% (i.e., 1 Mg N ha −1 ) more soil N compared to the CG sites over a 1 m depth. Additionally, the stocks' difference was mostly in the mineral-associated organic matter fraction in the A-horizon, suggesting long-term persistence of soil C in AMP grazing farms. The higher N stocks and lower 15 N abundance of AMP soils also point to higher N retention in these systems. These findings provide evidence that AMP grazing is a management strategy to sequester C in the soil and retain N in the system, thus contributing to climate change mitigation. Highlights: Adaptive multi-paddock grazing (AMP) can increase soil carbon (C) stocks. We found 13% more soil C on farms under AMP compared to conventional grazing (CG). In AMP, C shifted to more persistent organic matter, suggesting long-term C storage. We found 9% more soil nitrogen on farms practicing AMP compared to CG. Findings show that AMP grazing is a management strategy to sequester C and retain N.